Sex-biased expression of selected chromosome x-linked microRNAs with potent regulatory effect on the inflammatory response in children with cystic fibrosis: A preliminary pilot investigation - Deny, Maud; Popotas, Alexandros; Hanssens, Laurence; Lefèvre, Nicolas; Arroba Nuñez, Luis Alexis; Ouafo, Ghislaine Simo; Corazza, Francis; Casimir, Georges; Chamekh, Mustapha (Frontiers in Immunology, 2023)
Previous studies have reported sex disparity in cystic fibrosis (CF) disease, with females experiencing more pulmonary exacerbations and frequent microbial infections resulting in shorter survival expectancy. This concerns both pubertal and prepubertal females, which is in support to the prominent role of gene dosage rather than the hormonal status. The underlying mechanisms are still poorly understood. The X chromosome codes for a large number of micro-RNAs (miRNAs) that play a crucial role in the post-transcriptional regulation of several genes involved in various biological processes, including inflammation. However, their level of expression in CF males and females has not been sufficiently explored. In this study, we compared in male and female CF patients the expression of selected X-linked miRNAs involved in inflammatory processes. Cytokine and chemokine profiles were also evaluated at both protein and transcript levels and cross-analyzed with the miRNA expression levels. We observed increased expression of miR-223-3p, miR-106a-5p, miR-221-3p and miR-502-5p in CF patients compared to healthy controls. Interestingly, the overexpression of miR-221-3p was found to be significantly higher in CF girls than in CF boys and this correlates positively with IL-1β. Moreover, we found a trend toward lower expression in CF girls than in CF boys of suppressor of cytokine signaling 1 (SOCS1) and the ubiquitin-editing enzyme PDLIM2, two mRNA targets of miR-221-3p that are known to inhibit the NF-κB pathway. Collectively, this clinical study highlights a sex-bias in X-linked miR-221-3p expression in blood cells and its potential contribution to sustaining a higher inflammatory response in CF girls.